Sustaining metal–organic frameworks for water–gas shift catalysis by non-thermal plasma - Shaojun Xu (2019)
© 2019, The Author(s), under exclusive licence to Springer Nature America, Inc. The limited thermal and water stability of metal–organic frameworks (MOFs) often restricts their applications in conventional catalysis that involve thermal treatment and/or use of water. Non-thermal plasma (NTP) is a promising technique that can overcome barriers in conventional catalysis. Here we report an example of an NTP-activated water–gas shift reaction (WGSR) over a MOF (HKUST-1). Significantly, the exceptional stability of HKUST-1 was sustained under NTP activation and in the presence of water, which led to a high specific rate of 8.8 h −1 . We found that NTP-induced water dissociation has a twofold promotion effect in WGSR, as it facilitates WGSR by supplying OH and sustains the stability and hence activity of HKUST-1. In situ characterization of HKUST-1 revealed the critical role of open Cu sites in the binding of substrate molecules. This study paves the way to utilize MOFs for a wider range of catalysis.